Frequency of Rheumatoid Factor Positivity in Patients of Rheumatoid Arthritis Report of 95 cases from Lahore, Pakistan - ASMA MUNIR, MONA AZIZ, ATIYA MAHBOOB, MANAAL AFZAAL (Journal of Fatima Jinnah Medical University, 2018)
Background: Rheumatoid arthritis is a chronic systemic autoimmune disease affecting primarily joints. Rheumatoid factors are autoantibodies reactive with Fc portion of Ig G. Presence of rheumatoid factor can be used to confirm the diagnosis in individuals with a suggestive clinical presentation. Objectives: To determine the frequency of rheumatoid factor positivity in patients with rheumatoid arthritis. Study Design: Descriptive case series. Place and duration of study: Department of Medicine, Shaikh Zayed Medical Institute, Lahore from 01- 01-13 to 30-06-13. Subjects and Methods: Ninety five patients with rheumatoid arthritis of both genders above fifteen years of age fulfilling the ACR 2010 criteria were evaluated for presence of rheumatoid factor in blood. Results: There were 14 (14.7%) males and 81 (85.3%) female patients, male to female ratio was 1:5.8. Mean age of the patients was 42.38 ±10.7 years. 76 (80%) tested positive for Rheumatoid Factor IgM. Conclusion: Rheumatoid factor positivity in rheumatoid arthritis is quite common. Females are more commonly affected.